Three new and two known free-living marine nematode species of the family Ironidae from the East China Sea - Chen, Yu Zhen; Guo, Yu Qing (Zootaxa, 2015)
Three new and two known species of free-living marine nematodes of the family Ironidae from the East China Sea are described and illustrated. Conilia sinensis sp. nov. is identified by the relatively large body size (1883–2399 µm); the well developed lips; the number, shape and length of spicule (single and striated, length 87–100 µm as arc); the shape of telamon; the number of supplements (1). Pheronous donghaiensis sp. nov. is characterized by its sharp tail point; caudal gland absent; buccal cavity armed with four big solid teeth and rows of minute denticles; spicules stout, with central septum at proximal end, male caudal region with two rows of small conical subventral papillae. Trissonchulus latispiculum sp. nov. can be distinguished by its head not set off from remaining body, tail short and blunt, buccal cavity with minute denticles, spinneret opening slightly ventrally, spicule broad and alate with central septum and head on proximal end. Trissonchulus benepapillosus (Schulz, 1935) and Trissonchulus oceanus Cobb 1920 which are first reported from China, are redescribed in detail with emphasis on new or hitherto poorly described morphological features. Types are deposited in the Institute of Oceanology, Chinese Academy of Sciences.